(untitled) (Latakia University Journal -Biological Sciences Series, 2021)
The research dealt with a typical study of the consumption of bread commodity in the governorate of Lattakia (city and countryside), through the implementation of a written questionnaire, distributed randomly to individuals (representing families) who wished to participate, according to which 12 questions were asked, four of them related to demographic variables (residence, educational status) Work, number of family members) and eight of them are related to economic livelihoods (average income, preferred type of bread, the reason for this type preference, how bread is secured? What is the reason for resorting to this method of providing bread? Are there any residues of bread that do not consume? Can the required quantity of it be purchased? What is the main source of bread?). Descriptive statistical analysis methods were used, and the results were extracted depending on the SPSS program to analyze the study data. It included frequencies, percentages, and the weighted arithmetic mean according to Likert scale, in addition to the correlation coefficient, including the determination coefficient. The results showed that demographic variables play a statistically significant role, and are related to the pattern of supply of this food commodity. It was also found that there are high correlation coefficients values ​​(higher than 0.80) between values ​​related to demographic variables, and each of them is individually correlated with the answers to the eight aforementioned questions, and it was expressed in a mathematical relationship of the second degree. The correlation between the values ​​present in the answers to the demographic variables questions and the answers to the economic living variables questions within the multiple correlation concept (multiple regression) also gave very high values ​​(higher than 0.95).